Future Prediction of Foot-And-Mouth Disease (FMD): An Industrial Perspective - Muhamad Reza Pahlevi; Dikky Indrawan; Chaerul Basri (Eduvest - Journal of Universal Studies, 2024)
The global livestock industry is significantly threatened by foot-and-mouth disease (FMD). The re-emergence of FMD outbreaks in Indonesia is one example of the epidemiological cycle in a region. This study aimed to analyze the future industry of foot-and-mouth disease. This qualitative study used a secondary data processing that includes the collection, analysis, and interpretation of information to identify trends, challenges, and opportunities that may emerge by using the foresight industry analysis approach and the Generic Foresight Process (GFP) stage framework. Industry foresight analysis identified changing trends of technological, regulatory, geopolitical, demographic, and lifestyle. Several possibilities were identified through the GFP framework, which was conducted by identifying several possibilities based on looking and analyzing what is happening, what is really happening, what might happen in the future, what we would like to happen, and what we might need to do. The results of the industry foresight analysis showed that an FMD vaccine was essential for farmers to open international market access and as a sustainable disease control strategy. The technology aspect played a vital role as the key to competition in the industry in the future. The industry will compete to create an FMD vaccine that best suits the existing market challenges. The results of the GFP framework analysis showed that eradicating FMD worldwide still requires a long and extensive process and is predicted to continue until 2050.